2019
DOI: 10.1007/s12529-019-09781-8
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Deviation of Fairness Perceptions from Group Average and Serious Psychological Distress in Japanese Worksites: a Cross-Sectional Study

Abstract: Background Workers with deviating fairness perceptions are likely to be excluded and become isolated at worksites, leading to psychological distress. The study aimed to examine the cross-sectional association between deviation of fairness perception from the group average and serious psychological distress in Japanese worksites. Methods Secondary data analysis of an existing Japanese occupational cohort data using a multilevel logistic regression model was conducted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 57 publications
4
9
0
Order By: Relevance
“…This certainly causes disappointment and anger that may lead to psychological distress. This assumption is in line with the findings of previous empirical studies, showing that formal justice has a significant effect on psychological pressure [ 11 , 15 ]. Based on the empirical findings and assumptions that have been built, alternative hypotheses are proposed as follows:…”
Section: Literature Reviewsupporting
confidence: 91%
See 1 more Smart Citation
“…This certainly causes disappointment and anger that may lead to psychological distress. This assumption is in line with the findings of previous empirical studies, showing that formal justice has a significant effect on psychological pressure [ 11 , 15 ]. Based on the empirical findings and assumptions that have been built, alternative hypotheses are proposed as follows:…”
Section: Literature Reviewsupporting
confidence: 91%
“…Excessive negative emotional responses might lead to serious psychological suffering in a person [ 13 , 14 ]. As specialists have pointed out, injustice has an impact on psychological discomfort [ 15 ]. Unfortunately, little research has been done on the effects of formal and social justice on psychological discomfort, particularly in the realm of organizational justice.…”
Section: Introductionmentioning
confidence: 99%
“…For example, low levels of OJ have been suggested as an indicator of high job demands [43], procedural justice could be considered a measure of job control [32], and the distributive justice dimension has been seen as an analog of the ERI model [64]. However, the OJ model aims to capture the relational and administrative dimensions of the workplace environment [28], which is a relevant difference from other theoretical models and a key point to understanding the diverse impact that injustice can have among occupations or cultures.…”
Section: Discussionmentioning
confidence: 99%
“…However, Noblet et al [81] found that this association was significant only for the interpersonal justice dimension in a sample of Australian police officers. On the other hand, Yokouchi and Hashimoto [28] studied the deviation from the justice group mean as an alternative pathway by which OJ could affect health, finding that both low deviation and high deviation from the group mean in the case of interactional fairness and only high deviation in the case of procedural justice were positively associated with psychological distress.…”
Section: Organizational Justice and Job Stress: Cross-sectional Studiesmentioning
confidence: 99%
See 1 more Smart Citation